Trends of Visual Arts Professionals in the Kingdom of Saudi Arabia towards Curator - Yusra Saeed Al-Qahtani (الاكاديمي)
The current research aims to identify the concept of the artistic curator and to clarify the trends of specialists in the visual arts in the Kingdom of Saudi Arabia towards the artistic curator. The importance of the research lies in shedding light on the artistic curator and his historical origins. The research may contribute with its theoretical and cognitive material to enriching the Arab library on this topic, as this research is one of the first Arab research in this field, according to the researcher's knowledge. The research used the descriptive and analytical approach, and the research reached several results, the most important of which are: The association of the artistic curator in his historical beginnings with museums, and the care and classification of collections were his first official roles. The results of the research showed in general a high agreement among specialists on the positive role of the artistic curator in the visual arts in the Kingdom of Saudi Arabia.